2021
DOI: 10.1186/s42774-021-00086-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of conventional and air-jet wheel deflectors for drag reduction of the DrivAer model

Abstract: Aerodynamic drag is a large resistance force to vehicle motion, particularly at highway speeds. Conventional wheel deflectors were designed to reduce the wheel drag and, consequently, the overall vehicle drag; however, they may actually be detrimental to vehicle aerodynamics in modern designs. In the present study, computational fluid dynamics simulations were conducted on the notchback DrivAer model—a simplified, yet realistic, open-source vehicle model that incorporates features of a modern passenger vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…As a result of their research, they found that conventional wheel deflectors only reduced wheel drag but increased overall drag by close to 10%. They found that air-jet wheel deflectors, on the other hand, reduced drag by up to 1.5% at velocities of 35 m/s and above [8]. Khosravi et al [9] investigated the effects of the use of deflectors and cabin blades on heavy commercial vehicle drag.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result of their research, they found that conventional wheel deflectors only reduced wheel drag but increased overall drag by close to 10%. They found that air-jet wheel deflectors, on the other hand, reduced drag by up to 1.5% at velocities of 35 m/s and above [8]. Khosravi et al [9] investigated the effects of the use of deflectors and cabin blades on heavy commercial vehicle drag.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wolf [7] has shown that using the airflow ducted from front-mounted heat exchangers and deflected vertically downwards forward of the front wheels had a benefit on the 1997 model of the Porsche 911, although the improvement in drag coefficient was not quantified. Two recent CFD studies conducted by Nabutola and Boetcher [8,9] to investigate air jet wheel spoilers on a simplified body and a DrivAer model concluded in both cases that there were no drag benefits available.…”
Section: Introductionmentioning
confidence: 99%